2023
DOI: 10.1039/d3cc03829g
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical regulation of macrocyclic arenes with flipping-induced inversion of planar chirality

Ting Zhao,
Wanhua Wu,
Cheng Yang

Abstract: Studies on various macrocyclic arenes have received increasing attention due to their straightforward syntheses, convenient derivatization, and unique complexation properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Chirality sensing with macrocyclic arenes, such as pillar[ n ]arenes (P[ n ]), is particularly attractive because of their versatile binding ability and spectral response generated by the aromatic subunits. 5,25 P[ n ] may adopt either R p or S p conformers in the solution, which could rapidly interconvert in the solution via the flipping-induced inversion of planar chirality (FIIPC). 14 We and others have recently demonstrated that the complexation of a chiral guest will shift the R p or S p conformers of P[5]s and lead to strong ECCD signals, which is promising in application of chirality sensing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chirality sensing with macrocyclic arenes, such as pillar[ n ]arenes (P[ n ]), is particularly attractive because of their versatile binding ability and spectral response generated by the aromatic subunits. 5,25 P[ n ] may adopt either R p or S p conformers in the solution, which could rapidly interconvert in the solution via the flipping-induced inversion of planar chirality (FIIPC). 14 We and others have recently demonstrated that the complexation of a chiral guest will shift the R p or S p conformers of P[5]s and lead to strong ECCD signals, which is promising in application of chirality sensing.…”
mentioning
confidence: 99%
“…Supramolecular chirality has been attracting wide attention and has given rise to many intriguing research topics, such as chirality induction, transfer, sensing, memory and amplification. 1–8 Supramolecular chirality sensing is promising for detecting absolute configuration and optical purity based on spectroscopic methods, including UV/Vis spectra, fluorescence, NMR and circular dichroism (CD) spectroscopies. 9–13 Compared to conventional chromatographic techniques, supramolecular chirality sensing offers the benefit of rapid and inexpensive high-throughput screening.…”
mentioning
confidence: 99%
“…16 P [5]s possess R p (R p , R p , R p , R p , R p ) and S p (S p , S p , S p , S p , S p ) planar chiral conformers which typically interconvert through the flipping-induced inversion of planar chirality (FIIPC). 17 The complexation of a chiral guest with P [5] could shift the racemic equilibrium of the R p and S p conformers, thereby inducing significant circular dichroism (CD) responses. Moreover, the induced enantiomeric excess can be memorized by strategically controlling the racemization kinetics of the conformers through adjustments to the steric hindrance of side chain groups.…”
mentioning
confidence: 99%
“…Among these, pillar[5]­arene (P[5]) and its derivatives stand out for their efficient sensing and recognition of diverse chiral guests . P[5]­s possess R p ( R p , R p , R p , R p , R p ) and S p ( S p , S p , S p , S p , S p ) planar chiral conformers which typically interconvert through the flipping-induced inversion of planar chirality (FIIPC) . The complexation of a chiral guest with P[5] could shift the racemic equilibrium of the R p and S p conformers, thereby inducing significant circular dichroism (CD) responses.…”
mentioning
confidence: 99%
“…16 Composed of five hydroquinone units connected by methylene at the para-position, pillar [5]arenes have pillar-like structures [17][18][19][20][21] The symmetrical structures and easy functionalization endow pillar [5]arene with good properties in host-guest chemistry. [22][23][24][25][26][27] Owing to the significant efforts of scientists, numerous stimuli-responsive host-guest recognition motifs of pillar [5]arenes have been constructed and further utilized in the production of various materials, including pillar [5]arene-based supramolecular polymers and supramolecular amphiphiles. [28][29][30][31][32] In stark contrast, only a limited number of attempts have been made to investigate fluorescence properties of pillar [5]arene-based host-guest systems.…”
mentioning
confidence: 99%